Interpreting ‘Most Serious Crimes’ under Article 6(2) of ICCPR - Devita Kartika Putri (Fakultas Hukum Universitas Gadjah Mada, 2019)
AbstractArticle 6 of the International Covenant for Civil and Political Rights protects the right to life. Meanwhile, Article 6(2) stipulates an exception where death penalty may only be imposed for the ‘most serious crimes.’ The Human Rights Committee had previously provided that ‘most serious crimes’ exclude other crimes which do not result in loss of life regardless of how severe the crime may be, including—crimes that threaten national security. In this regard, this Article will attempt to explore the scope of ‘most serious crimes’ by means of interpretation and margin of appreciation. IntisariPasal 6 Kovenan Internasional tentang Hak Sipil dan Politik melindungi hak untuk hidup. Sementara itu, Pasal 6 (2) menetapkan pengecualian di mana hukuman mati hanya dapat dikenakan untuk 'kejahatan paling serius.' Komite Hak Asasi Manusia sebelumnya menetapkan bahwa 'kejahatan paling serius' mengecualikan kejahatan lain yang tidak mengakibatkan hilangnya nyawa terlepas dari seberapa parah kejahatan itu, termasuk — kejahatan yang mengancam keamanan nasional. Dalam hal ini, Pasal ini akan mencoba untuk mengeksplorasi ruang lingkup 'kejahatan paling serius' dengan cara interpretasi dan margin of appreciation.